Air pollutants and outlays vs quality of life in Poland and the welfare economics - Pakulska, Jolanta (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The paradigms of the welfare economics are considered to be the basis of modern considerations on the measurement of quality of life. Today, there is no doubt that the quality of the environment, and especially the air quality that man breathes, is an essential element of the quality of life. Environmental problems, including air quality, often contribute to the failure of economic policies aimed at maximizing people’s well-being. Therefore, the state of all elements of the environment is important for the effectiveness of the implementation of the welfare economics and ensuring a satisfactory standard of living of the society. The last 20 years in Poland have been a time of catching up with many years of neglect in the area of the natural environment. It is a process that takes time and there is no possibility to achieve a high environmental quality of life in the short term. There is no disputing that measures were taken during this period to improve the environmental quality of life. Aim: The study focused on air quality, as it is an element of the environment that cannot be cleaned before use. The aim of the study is to check whether the measures taken to reduce emissions of pollutants into the atmospheric air have been effective and to what extent it was possible to improve its condition and to improve the environmental quality of life of the Polish society in terms air the air we breathe. Results: The results of the analysis in dynamic terms indicate that the quality of life in Poland during the transition, taking into account the emission of the main air pollutants, has improved.